ANALYSIS OF THE USE OF MEDUME BOARDS FOR LEARNING IN ELEMENTARY SCHOOLS ON DATA PROCESSING MATERIAL - evangeline yuana elvida; melda setialista; ninda putriayu; ni wayan deliani; syifa nabila (Journal of Pedagogical Content Knowledge, 2025)
This research aims to examine the effect of using Medume board media on increasing fourth grade elementary school students' understanding of data processing material. Medume Board, a visual-based learning aid, is designed to make it easier for students to understand the concepts of mean, mode, and median. The method used in this research is descriptive qualitative with data collection techniques through literature studies from various sources, such as books, journals and scientific articles. This research shows that using the Medume board can improve students' abilities in processing and analyzing data through interactive and concrete visualization. In addition, Medume boards are also effective in increasing students' active participation, development of analytical skills, and learning motivation. The research results are expected to contribute to the development of innovative learning media in the field of basic mathematics, especially in data processing material. Medume boards not only act as visual aids, but also as tools that support the development of critical thinking and problem solving skills. By utilizing simple but effective data visualization, students can more easily understand basic statistical concepts. In addition, this research illustrates that the integration of visual media such as Medume boards into the learning process can serve as a model for other teaching methods in subjects that require an understanding of abstract concepts.